PETRONAS Chemicals Group Berhad / Nur Amisha Abdul Razak - Abdul Razak, Nur Amisha (Faculty of Business and Management, 2023)
This executive summary provides an overview of my journey in joining the Petronas Internship Program, highlighting its objectives and key components. Petronas Chemicals Group Berhad being the leading integrated Petro chemicals producer in Malaysia and one of the largest in Southeast Asia is also committed to developing young talents and providing them with valuable industry experience through its internship program.